KESESUAIAN STANDAR KOMPETENSI DAN KOMPETENSI DASAR MATA PELAJARAN IPA UNTUK PENGEMBANGAN IDEATIONAL LEARNING PADA SMP RSBI KELAS VII DI PROPINSI DIY - Jumadi, Bambang Subali, dan Das Salirawati (Jurnal Cakrawala Pendidikan, 2009)
AbstractThe Relevance of the Standards of Competence and Basic Competence inNatural Science Subjects to the Development of Ideational Learning in Year VII ofPilot International Standard Junior High Schools in Yogyakarta Special TerritoryProvince. This study aims to investigate the relevance of the standards ofcompetence and basic competence to the development of ideational learning inPilot International Standard Junior High Schools (PISJHSs). This study wasconducted in Yogyakarta Special Territory Province and employed a surveymethod involving 36 teachers of Year VII of PISJHSs. The survey instrument was aquestionnaire that the researchers developed. The results show that all standards ofcompetence and basic competence for Year VII students in semesters 1 and 2 arecapable of developing ideational learning. Therefore, it is not necessary to add newstandards of competence and basic competence to develop ideational learning.However, it is still necessary to add indicators leading ideational learning to thebasic competence in the syllabus of the school-based curriculum in PISJHSs.Keywords: standards of competence, basic competence, ideational learning